Endometrial scratching and intralipid treatment—no general recommendations - Mrosk, Paolina; Sandi-Monroy, Nathallie; Gagsteiger, Friedrich; Friedl, Thomas Wolfram Paul; Hancke, Katharina; Bundschu, Karin (Frontiers in Reproductive Health, 2024)
ObjectivesEndometrial scratching (ES) and/or intravenous intralipid therapy (in cases of increased uterine natural killer cells, uNKs) are still conducted in several fertility centers as “add-on” treatments in patients undergoing ART, although convincing evidence for beneficial effects is lacking.Study designIn this retrospective study, associations between ES treatment or additional intralipid therapy and pregnancy and live birth rates of 1,546 patients undergoing 2,821 IVF-/ICSI-treatment cycles with fresh or frozen embryo transfers in a German fertility-center between 1st January 2014 and 31th May 2017 were analyzed.ResultsOverall pregnancy and live birth rates for all 2,821 treatment cycles (468 cycles with ES) were 32.8% and 23.5%. There were no statistically significant differences in pregnancy or live birth rates between first treatment cycles with and without ES (p = 0.915 and p = 0.577) or between second cycles following an unsuccessful first cycle with and without ES (p = 0.752 and p = 0.623). These results were confirmed using multivariable generalized estimating equations (GEE) models accounting for non-independency of multiple treatment cycles per patients that included all cycles and showed no significant effect of ES on pregnancy (p = 0.449) or live birth rates (p = 0.976). Likewise, a GEE model revealed no significant effect of intralipid treatment on pregnancy (p = 0.926) and live birth rates (p = 0.727).ConclusionsOur results reveal no evidence that ES increases the pregnancy or live birth rates in women undergoing their first or further IVF cycle with fresh or frozen embryo transfer. Intralipid treatment was also not beneficial. Even if patients explicitly ask for it, these procedures are not recommended outside of clinical studies.